Are Islamic Branding and Halal Awareness Relevant? A Study of Annuqayah Santri's Purchasing Decisions on Wardah Cosmetics - Sumita; Maksum (Airlangga Journal of Innovation Management, 2024)
Cosmetics have become an important part of women's lives, including teenage santriwati at Pondok Pesantren Annuqayah, who use cosmetics not only to maintain skin health but also to boost self-confidence. Indonesia, as the second largest market for halal cosmetics, is a relevant place to examine the influence of Islamic branding, halal awareness, trust, and product quality on purchasing decisions. Islamic branding is expected to give consumers a sense of trust that the product is halal. Halal awareness also influences consumers in choosing halal-labeled products as part of compliance with sharia. The research uses a quantitative approach with a purposive sampling technique with the criteria that female Santri are at least 15 years old, Wardah cosmetic users, and have used it for the past year. The data were analysed using multiple regression with a sample of 100 respondents obtained through filling out a questionnaire by Santri, which was then carried out using a using a validity test, a classical assumption test, and hypothesis testing using multiple linear regression with the help of SPSS. The results showed that partially Islamic branding (0.029), trust (0.003), and product quality (0.001) have an influence on the purchasing decisions of Pondok Pesantren Annuqayah Santri on Wardah cosmetic products, while halal awareness (0.062) has no effect. These results provide an understanding of the behaviour of santri through an Islamic economic approach. Further research can increase the number of observations about the behaviour of Santri at the Islamic Boarding School.